PENGARUH FINANCIAL INDICATORS DAN CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS - Rosa Arlina Nurulita; Akhmad Samsul Ulum; Amalia Ilmiani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
Financial distress occurs before a company actually goes bankrupt, due to theinability to pay financial obligations that have matured. This study intends toexamine the effect of corporate governance and financial indicators which includefirm performance, financial leverage, firm size, and lagged financial distress onfinancial distress. The sample was taken using a purposive technique from retailtrading companies that publish financial reports on the Indonesia Stock Exchange(IDX) during the 2015-2019 period. A total of 85 data on retail trading companieswere obtained and then tested using logistic regression techniques. The results ofthis study indicate that firm performance has a negative effect on financial distress.Financial leverage and lagged financial distress have a positive effect on financialdistress. Firm size and corporate governance have no effect on financial distress.